Musical Memory - Žerak Urbanc, Talija (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines musical memory, the ability to store and retrieve musical elements such as melodies, rhythms, and lyrics. It emphasizes the role of emotional content in music, which enhances the consolidation and recognition of musical memories. Research indicates that musical memory relies on both implicit and explicit mechanisms, with experience and musical training significantly improving memory retention. The findings highlight that music's emotional and tonal qualities strengthen long-term memory, while musical training not only enhances cognitive abilities but also influences brain structure. For music education, recommended strategies include incorporating emotionally engaging pieces, employing analytical methods, and encouraging targeted practice, all of which foster improved memorization and pattern recognition in music.